An Analysis Of Metaphor In James Arthur Song’s Lyric - elia, Elia Putri Ribka; Sidabutar, Usman; Siahaan, Sahat Taruli (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2024)
This research discusses the analysis of metaphors contained in the lyrics of James Arthur's song on his 3rd album entitled